2010
DOI: 10.1038/emboj.2010.82
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear export receptor XPO-1 supports primary miRNA processing in C. elegans and Drosophila

Abstract: MicroRNA (miRNA) biogenesis proceeds from a primary transcript (pri-miRNA) through the pre-miRNA into the mature miRNA. Here, we identify a role of the Caenorhabditis elegans nuclear export receptor XPO-1 and the cap-binding proteins CBP-20/NCBP-2 and CBP-80/NCBP-1 in this process. The RNA-mediated interference of any of these genes causes retarded heterochronic phenotypes similar to those observed for animals with mutations in the let-7 miRNA or core miRNA machinery genes. Moreover, pre- and mature miRNAs bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 52 publications
4
62
0
2
Order By: Relevance
“…Previous studies showed that Exportin-1, an essential transport factor for certain proteins and RNAs, supports pri-miRNA processing in Caenorhabditis elegans and Drosophila, as well as shuttling of mature miRNA from the cytoplasm to the nucleus (28,41,42). Recently, we showed that Exportin-1 is involved in the nuclear export of a group of mammalian (m 7 G)-capped pre-miRNAs in proliferating cells (27).…”
Section: Exportin-1 Is Required For Processing Of Quiescence-induced mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that Exportin-1, an essential transport factor for certain proteins and RNAs, supports pri-miRNA processing in Caenorhabditis elegans and Drosophila, as well as shuttling of mature miRNA from the cytoplasm to the nucleus (28,41,42). Recently, we showed that Exportin-1 is involved in the nuclear export of a group of mammalian (m 7 G)-capped pre-miRNAs in proliferating cells (27).…”
Section: Exportin-1 Is Required For Processing Of Quiescence-induced mentioning
confidence: 99%
“…Exportin-1, the major factor responsible for the export of proteins from the nucleus, is also involved in the export of certain RNAs such as ribosomal RNAs, snRNAs, and mRNAs encoding some proteins involved in cell-cycle regulation (28,52). Previous studies in C. elegans and Drosophila showed that Exportin-1 is involved in pri-miRNA processing and biogenesis (41). Our findings demonstrate that Exportin-1 is also involved in the biogenesis of specific miRNAs in proliferating mammalian cells and that this activity is enhanced during quiescence.…”
Section: Exportin-1-dependent Mirna Biogenesis Occurs During Cellularmentioning
confidence: 99%
“…The best-characterized miRNA in C. elegans is let-7, which controls developmental timing. Mutations in let-7 block the transition from late larval to adult cell fates, in particular by fusion of seam cells, and animals often die from a bursting vulvae phenotype (Bussing et al 2010). Knockdown of XPO-1, or inhibition of the cap-binding complex (consisting of NCBP-1 and NCBP-2), which acts as an adaptor for XPO-1, causes similar developmental defects as well as a 50% reduction in mature let-7 miRNA, arguing that XPO-1 is likely the transport receptor of pre-miRNAs in C. elegans (Bussing et al 2010).…”
Section: Nuclear Localization and Nuclear Export Signalsmentioning
confidence: 99%
“…Article and publication date are at http://www.rnajournal.org/cgi/doi/10.1261/rna.2265710. miRNA biogenesis pathways has been recently indicated in Arabidopsis, and this has been extended to RNA silencing in animals (Gregory et al 2008;Kim et al 2008;Laubinger et al 2008;Gruber et al 2009;Sabin et al 2009;Büssing et al 2010). Connecting these two processes permits more robust and accurate regulation of gene expression, and further inquiry into the crosstalk is expected to reveal additional roles.…”
Section: Introductionmentioning
confidence: 99%